Hepatoprotective effect of Red Sea sponge extract against the toxicity of a real-life mixture of persistent organic pollutants. Issue 3 (4th May 2018) - Abd El Moneam, Nehad M.; Shreadah, Mohamed A.; El-Assar, Samy A.; De Voogd, Nicole J.; Nabil-Adam, Asmaa
ABSTRACT: The present study aims to evaluate the possible hepatoprotective effect of the Red Sea Hyrtios aff . erectus sponge extract against persistent organic pollutants (POPs). The induced hepatotoxicity effects were examined by using different POPs compounds, namely, α-hexachlorocyclohexane, β-hexachlorocyclohexane, γ-hexachlorocyclohexane, PCB 28, PCB 52, aldrin, o, p'-DDE, PCB 101, dieldrin, p, p'-DDE, o, p'-DDD, endrin, PCB 118, p, p'-DDD, p, p'-DDT, PCB 153, PCB 135, PCB 138 and PCB 180, extracted from sediments collected from Lake Mariout. The effects were assessed based on biochemical assays, where BALB/c albino mice (mean weight 28 ± 4 g) exposed to 130.6 mg/100 g b.w./d of POP mixtures were compared to control and induction groups. The POPs toxicity test was carried out on the BALB/c albino mice for one week. The POPs treated group had a significant increase in the levels of transaminases, ALT and AST. There was also a significant increase in serum bilirubin in response to POPs mixture toxicity. In contrast, the protective group revealed a non-significant increase in both aminotransferases and bilirubin level. The results indicate that POPs could act through free radical-induced oxidative stress. Furthermore, the hepatoprotective effect of sponge extract against POPs mixture is due to the presence of polyphenolic compounds in sponge. The present study revealed that polyphenolic compounds play a vital role in diminishing the hepatotoxicity, as confirmed by a decrease in liver toxicity.